Occupational mobility within and between skill clusters : an empirical analysis based on the skill weights approach - Geel, Regula [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2011)
"This paper applies Lazear's skill-weights approach (2009) to analyze the specificity of skill combinations of various occupations and its effects on occupational mobility and wages. The results show that the more specific an occupation, the smaller the probability of an occupational change. We also identify clusters of occupations characterized by similar skill combinations and find that employees in specific occupations have a comparatively higher probability of changing occupations within a skill cluster than between skill clusters. Moreover, occupational mobility within a skill cluster results in wage gains, while between clusters it results in wage losses. Therefore, the acquired skill combination and the resulting skill cluster, rather than the occupation per se, crucially determines mobility. Thus, for educational policies, it is more important to study whether a skill cluster is sustainable than an occupation." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; G 1.3.3.3 Mobilität; Humankapitaltheorie; Berufsausbildung; Berufliche Qualifikation; Spezialisierung; Berufliche Mobilität; Berufsverlauf; Berufswechsel; Einkommenseffekte